Mimesis and science: empirical research on imitation and the mimetic theory of culture and religion - Garrels, Scott R. (Studies Violence Mimesis and Culture, 2011)
Intro -- Contents -- Preface -- Chapter 1: Human Imitation: Historical, Philosophical, and Scientific Perspectives / Scott R. Garrels -- Part 1: Imitation in Child Development and Adult Psychology -- Chapter 2: From Universal Mimesis to the Self Formed by Desire / Jean-Michel Oughourlian -- Chapter 3: Out of the Mouths of Babes: Imitation, Gaze, and Intentions in Infant Research - the "Like Me" Framework / Andrew N. Meltzoff -- Chapter 4: Emotions and Mimesis / Paul Dumouchel -- Chapter 5: The Two Sides of Mimesis: Mimetic Theory, Embodied Simulation, and Social Identification / Vittorio Gallese -- Part 2: Imitation in Human Evolution, Culture, and Religion -- Chapter 6: Imitation, Communion, and Culture / Ann Cale Kruger -- Chapter 7: Imitation and Violence: Empirical Evidence and the Mimetic Model / Mark R. Anspach -- Chapter 8: Sacred Violence, Mimetic Rivalry, and War / Melvin Konner -- Chapter 9: Desire, Mimesis, and the Phylogeny of Freedom / William B. Hurlbut -- Chapter 10: Naturalizing Mimetic Theory / Jean-Pierre Dupuy -- Chapter 11: Mimesis and Science: An Interview with Rene Girard / Scott R. Garrels -- Contributors -- Index.